2017
DOI: 10.1111/apha.12835
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of left and right atrial fibroblasts reveals different collagen production activity and stress‐induced mitogen‐activated protein kinase signalling in rats

Abstract: Differences in profibrotic activity between LA and RA fibroblasts may be caused by different responses to mitogen-activated protein kinase signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Furthermore, TGF-β1 can induce other non-canonical signaling cascades independently of Smads, such as mitogen-activated protein kinase (MAPK) signaling pathways, including extracellular signal-regulated kinase 1/2 (ERK1/2), p38 MAPK and c-Jun N-terminal kinase (JNK) (9). Accumulating evidence has demonstrated that MAPK signaling plays a critical role in EcM synthesis and in the proliferation of cFs (10,11). Thus, pharmacological interventions in these signaling pathways could be considered as a promising therapeutic strategy against cardiac fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TGF-β1 can induce other non-canonical signaling cascades independently of Smads, such as mitogen-activated protein kinase (MAPK) signaling pathways, including extracellular signal-regulated kinase 1/2 (ERK1/2), p38 MAPK and c-Jun N-terminal kinase (JNK) (9). Accumulating evidence has demonstrated that MAPK signaling plays a critical role in EcM synthesis and in the proliferation of cFs (10,11). Thus, pharmacological interventions in these signaling pathways could be considered as a promising therapeutic strategy against cardiac fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…The study was approved on 8 May 2018 by Laboratory Animal Committee of Taipei Medical University (approval number: LAC-2017-0383). LA and RA cardiac fibroblasts were isolated from male Sprague–Dawley (SD) rats (weighing 300–350 g) by using a modified protocol [ 13 ]. Briefly, after the animals were euthanized, the hearts were rapidly mounted on a Langendorff apparatus and perfused with phosphate-buffered saline containing 25 U/mL type 2 collagenase (Sigma, St. Louis, MO, USA) at 37 °C for 35 min.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as described previously [ 13 ]. In brief, P1 LA and RA fibroblasts treated with or without ethylene glycol tetra-acetic acid (EGTA, 1 mmol/L, Sigma-Aldrich) or a Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) inhibitor (KN93, 10 μmol/L, Sigma-Aldrich) were lysed in a radioimmunoprecipitation assay buffer containing 150 mmol/L NaCl, 0.5% sodium deoxycholate, 1% NP40, 50 mmol/L Tris pH 7.4, 0.1% sodium dodecyl sulfate (SDS) and protease inhibitor cocktails (Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations